The polymeric nanofilm of triazinedithiolsilane capable of resisting corrosion and serving as an activated interface on a copper surface. Issue 8 (18th January 2016) - Wang, Yabin; Liu, Zhong; Dong, Yaping; Li, Wu; Huang, Yudong; Qi, Yutai
Abstract : It seems self-contradictory that a copper surface can resist corrosion and be activated concurrently. Abstract : It seems self-contradictory that a copper surface can resist corrosion and be activated concurrently. On the one hand, an activated surface has a high affinity for water (H2 O) and chloride ions (Cl − ), which significantly accelerate corrosion; on the other hand, only inert/unactivated/hydrophobic surfaces can exhibit outstanding corrosion resistance. This investigation concentrates on fabricating a novel multifunctional polymeric nanofilm that can resist corrosion and serve as an activated interface on a copper surface simultaneously, as well as revealing the functional mechanism of the nanofilm. A triazinedithiolsilane compound (TESPA) was self-assembled onto a copper surface with subsequent heating to obtain such a multifunctional interface. In order to study its protective ability, octadecyltrichlorosilane (OTS), which can yield substances that are hazardous to copper, was selected to be anchored, forming a bilayer of TESPA-OTS. To confirm the activating ability of the polymeric nanofilm, octyltriethoxysilane (OTES), as a friendly reagent, was grafted onto the surface (TESPA-OTES). Electrochemical tests were applied to determine the corrosion resistance of the bilayers, the contact angle (CA) was measured to monitor changes in the wetting properties/chemical groups, scanning electron microscopy (SEM) was performed to observe the morphologies, and energy-dispersive X-ray spectroscopy (EDS) was used to detect the chemical states. The results from comparative experiments show that OTS and OTES can be successfully anchored to the functionalized copper surface via SiOH groups that originated from the polymeric nanofilm; disulfide units (–SS–) and siloxane networks (SiOSi) efficiently protect the copper surface. In short, the investigation definitely proves that the polymeric nanofilm not only protects the copper, but also serves as an activated interface on the copper surface. This multifunctional interface is expected to open up possibilities for other OH-containing reagents to be anchored onto a copper surface in demanding research or industrial applications such as catalysis and coloring and paint processes that need a protective and activated medium for higher performance.